2020
DOI: 10.1016/j.tcb.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Associated Proteins in Tissue Repair

Abstract: The administration of (stem) cell-derived extracellular vesicles (EVs) promotes tissue repair through management of different inflammatory, proliferative and remodeling processes in the body. Despite the widely observed biological and therapeutic roles of EVs in wound healing and tissue repair, knowledge on how EVs activate recipient cells and which EV cargo is responsible for the subsequent functional effects is limited. Recent studies hint toward an important role for proteins as functional EV cargo. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 121 publications
0
70
1
Order By: Relevance
“…Beyond a signi cant ampli cation of exosomal ACE2 in the anti-SARS-CoV-2 e cacy in comparison to the puri ed rhACE2 proteins or its Fc-fusions 38 , we anticipate that the therapeutic e cacy of ACE2 + exosomes can be further potentiated through co-delivering additional anti-SARS-CoV-2 medicines, such as remdesivir 39,40 . Exosomes have been utilized as drug delivery systems with therapeutic potential against various disorders including infectious diseases and cancers 41,42 . Of note, exosomes derived from both plants and human specimen, such as dendritic cells and tumor cells, have been evaluated in multiple clinical trials and proven safe in human [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond a signi cant ampli cation of exosomal ACE2 in the anti-SARS-CoV-2 e cacy in comparison to the puri ed rhACE2 proteins or its Fc-fusions 38 , we anticipate that the therapeutic e cacy of ACE2 + exosomes can be further potentiated through co-delivering additional anti-SARS-CoV-2 medicines, such as remdesivir 39,40 . Exosomes have been utilized as drug delivery systems with therapeutic potential against various disorders including infectious diseases and cancers 41,42 . Of note, exosomes derived from both plants and human specimen, such as dendritic cells and tumor cells, have been evaluated in multiple clinical trials and proven safe in human [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Exosomes can also activate intracellular signaling pathways to trigger repair of target cells by directly acting at the cell surface without transferring their cargo. 19 Exosomes are also natural nanocarriers. Their phospholipid bilayer structure protects biologically active substances, such as growth factors and miRNA, for sustained release.…”
Section: Exosomes In Tissue Repairmentioning
confidence: 99%
“…Many studies have found that exosomes participate in cancer drug resistance [ 12 ], cutaneous wound healing [ 39 ], liver injury, and so on [ 40 ]. The cargos in EVs have been found to prevent cell death, modulate immune response, maintain vascular integrity, and promote cell activity [ 41 ]. Thus, attempts to recognize the underlying mechanisms of different EVs make it important for us to prevent this progression and seek means of addressing illness.…”
Section: Isolation Identification and Function Of Exosomesmentioning
confidence: 99%